Relationship between physical fitness and birth distribution on elite Japanese soccer players: A pilot study - Morishima, Y.; Oya, T.; Miyagi, O. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In the players` selection, it was reported that the number of players born in the first three months tend to be large compared with the player born in other months. However, there are little researches concerning the birth month for the player who belongs to Japan Professional Football League. This study was designed to examine the relationship between physical fitness and birth distribution on elite Japanese soccer players aged 13 - 15 years. Methods The subject were one thousand four hundred seventy players (aged: 13 - 15 years old) belongs to a professional soccer team in Japan. Their date of birth were divided into four periods of the year: April to June, July to September, October to December, January to March. Measurement item were height and weight as physique. Four items were measured to represent players` ability: 30m sprint time, Squat Jump, Counter Movement Jump and YO-YO Intermittent Recovery Test. Results & Discussion The date of birth distribution of professional soccer players in Japan were shown in Fig.1. The highest proportion of players was between April and June (U-13; 47%, U-14; 47%, U-15; 44%), and the lowest proportion was between January and March (U-13; 8%, U-14; 8%, U-15; 9%). In particular, those players born in the first three months between April and June were superior to the players in the last three months for the height, weight, 30m sprint time and jump ability. Conclusion.. It was suggested that high relevance is between physical fitness and birth distribution on elite Japanese soccer players aged 13 - 15 years.